2008
DOI: 10.1038/sj.bjc.6604678
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of dietary patterns and colorectal cancer among Singapore Chinese

Abstract: An influence of Western diet and lifestyle factors observed among Singapore Chinese may contribute to the population's marked rise in colorectal cancer incidence over the past two decades. Thus far, however, there is little evidence for individual nutrients and foods as major contributing factors in this population. We evaluated whether patterns of food intake were associated with colorectal cancer in a population-based cohort of 61,321 Singapore Chinese that was established in 1993 -98. Two dietary patterns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 29 publications
(39 reference statements)
5
86
0
Order By: Relevance
“…The use of dietary patterns has thus been proposed to analyze the association between diet and cancer, given their ability to capture the variations in overall food intake. 9 In particular, a few case-control [10][11][12][13][14][15][16] and cohort [17][18][19][20][21] studies have investigated the effect of diet on colorectal cancer identifying dietary patterns through factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dietary patterns has thus been proposed to analyze the association between diet and cancer, given their ability to capture the variations in overall food intake. 9 In particular, a few case-control [10][11][12][13][14][15][16] and cohort [17][18][19][20][21] studies have investigated the effect of diet on colorectal cancer identifying dietary patterns through factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2]. Since then, 5 new prospective cohort studies on vitamin D intake and CRC have been published (3)(4)(5)(6)(7), substantially increasing the evidence base available, but no updated doseresponse meta-analyses have been published on vitamin D intake. In 2009, Huncharek and colleagues performed the highest versus lowest meta-analysis of vitamin D intake and CRC and observed no statistically significant results (8).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies using exploratory factor analysis, have found that the Western pattern, characterized by red meat, processed meat, and the intake 1 , María Mendilaharsu 1 of eggs, has been positively associated with an increased risk of colon cancer (Randall et al, 1992;Slattery et al, 1998;Terry et al, 2001;Fung et al, 2003;Kim et al, 2005;Kesse et al, 2006;Dixon et al, 2004;Flood et al, 2008;Butler et al, 2008). To our knowledge, the role of nutrients in colorectal cancer has been explored through factor analysis in only one study conducted in Italy (Bravi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%